Queer Politics in Hindu Mythology: Locating Misrepresentation of Gender Fluidity in Amar Chitra Katha’s "Krishna" and other Titles - Dhar, Sreyoshi; Moushumi Kandali (Tattva Journal of Philosophy, 2024)
In India, the Vedas and other Hindu mythologies mention of third-gendered gods and even some that manifest all the three genders, along with mentions of gods that cross-dress, without any gender transition. One such multi-faceted character in Hindu mythology is the character of Krishna. While commentaries on Krishna by brahmin scholars portray him as a masculine warrior, the non-brahmin commentaries such as Shrimad Bhagavatam, see Krishna in feminine terms. Krishna in such commentaries is seen as a cross-dressing, gender fluid being who is immensely comfortable in both his masculine and feminine identities, and adheres to both and none simultaneously. However, most retellings and adaptations of Krishna’s lore depict him as alluding to the former masculinist identity, thus completely subduing and ignoring the queer aspects of his character. Such focused partial exposure, unfortunately, begins at a very young age through the works of children’s literature. One such very influential franchise in India is the Amar Chitra Katha. In this paper, I would attempt to analyze the titles of Krishna- Retold from the Bhagawat Puran and Bhagawat- The Krishna Avatar thoroughly and explore how every aspect of it is changed or omitted in order to provide a heteronormative and heterosexual narrative.